A rare complication of a rare disease: Pericarditis due to ruptured pericardial cyst. Issue 8 (10th July 2020) - Lak, Hassan; Shah, Rohan; Verma, Beni R.; Xu, Bo
Abstract: Pericardial cysts are considered rare incidental findings, which are generally asymptomatic in nature. Occasionally, patients may represent with chest discomfort, dyspnea, or palpitations. Pericarditis related to a ruptured pericardial cyst has not been previously reported in the literature. Here, we report the case of a 62‐year‐old man who developed acute pericarditis as a result of a ruptured enlarging pericardial cyst.